Huntingtin gene intermediate alleles influence the progression from subjective cognitive decline to mild cognitive impairment: A 14‐year follow‐up study. (28th February 2022) - Mazzeo, Salvatore; Emiliani, Filippo; Bagnoli, Silvia; Padiglioni, Sonia; Conti, Vittoria; Ingannato, Assunta; Giacomucci, Giulia; Balestrini, Juri; Ferrari, Camilla; Sorbi, Sandro; Nacmias, Benedetta; Bessi, Valentina
Abstract: Background and purpose: Huntingtin ( HTT ) is a gene containing a key region of CAG repeats. HTT alleles containing from 27 to 35 CAG repeats are termed intermediate alleles (IAs). We aimed to assess the effect of IAs on progression of cognitive impairment in patients with subjective cognitive decline (SCD). Methods: We included 106 patients with SCD. All the patients underwent neuropsychological assessments and blood sample collection at baseline. Patients were followed up for a median (interquartile range) time of 13.75 (8.17) years. We genotyped APOE and HTT at the end of the follow‐up. Results: Eleven out of 106 patients (10.38%, 95% confidence interval [CI] 4.57–16.18) were carriers of IAs (IA + ). During the follow‐up, 44 patients (41.51%, 95% CI 32.13–50.89) progressed to mild cognitive impairment (MCI; p‐SCD group), while 62 patients (58.49%, 95% CI 49.11–67.87) did not (np‐SCD group). Rate of progression to MCI was associated with IAs, age at baseline, and APOE ɛ4. We dichotomized age at baseline (<60 years = younger patients [YP], >60 years = older patients [OP]) and then classified patients into four groups: YP/IA –, YP/IA +, OP/IA –  and OP/IA + . The OP/IA +  group had a higher proportion of patients with progression from SCD to MCI (85.71%, 95% CI 59.79–100) as compared to the YP/IA –  group (28.57%, 95% CI 13.60–43.54, χ 2  = 15.25; p  < 0.001) and the OP/IA –  group (45.00%, 95% CI 32.41–57.59, χ 2  = 7.903; p  = 0.005). We classified patients according to APOE and IA as: ɛ4 – /IA –, ɛ4 – /IA +, ɛ4 + /IA –, ɛ4 + /IA + . The proportion of patients with progression in the ɛ4 + /IA +  group (100%) was higher as compared to the ɛ4 – /IA –  group (33.33%, 95% CI 21.96–44.71, χ 2  = 14.43; p  < 0.001) and ɛ4 + /IA –  (55.56%, 95% CI 36.81–74.30, χ 2  = 4.60; p  = 0.032). Conclusions: Intermediate alleles interact with age and APOE ɛ4, increasing the risk of progression to MCI in SCD patients.